Tinjauan Etis terhadap Rekayasa Genetika dalam Kajian Human Cloning - Darwin Sibarani (Lumen: Jurnal Pendidikan Agama Katekese dan Pastoral, 2024)
Biotechnology has brought extraordinary advances in health, agriculture, and scientific research, but it has also raised complex ethical challenges, especially in human cloning technology. In the context of biotechnology, cloning refers to the creation of a genetic copy of an organism, and although animal cloning has been successfully carried out for research purposes and increasing agricultural yields, human cloning remains a controversial issue. Ethically, human cloning raises a number of questions regarding human rights, identity, and the potential misuse of this technology for unethical purposes, such as genetic programming or the creation of "design babies." This article examines various ethical views regarding the limits of the use of biotechnology, with a focus on human cloning. The research uses qualitative methods through literature study. Despite the efforts of scientists to continue developing human cloning, as Christians we must take a stand on this matter. The Bible teaches that God as the first initiator created humans in the image and likeness of God, in this case creating humans, God's sole right and obligation.